2023
DOI: 10.3390/microorganisms11030722
|View full text |Cite
|
Sign up to set email alerts
|

Use of Shotgun Metagenomics to Assess the Microbial Diversity and Hydrocarbons Degrading Functions of Auto-Mechanic Workshops Soils Polluted with Gasoline and Diesel Fuel

Abstract: Bioaugmentation is a valuable technique for oil recovery. This study investigates the composition and functions of microbial communities in gasoline- and diesel-contaminated soils of garages Matoko (SGM) and Guy et Paul (SGP) originating from auto mechanic workshops as well as the concentration of soil enzymes β-glucosidase, β-glucosaminidase, and acid phosphatase. The work aimed to evaluate the presence of petroleum-hydrocarbon-degrading bacteria for the development of foreseen bioremediation of oil-contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(79 reference statements)
1
0
0
Order By: Relevance
“…Research by Borowik et al [35], Borowik et al [19], and Wyszkowska et al [36] indicate that diesel oil stimulates the activity of soil enzymes. Similar results were reported by Goma-Tchimbakala et al [37], who observed high activities of β-glucosidase, β-glucosaminidase, and acid phosphatase in soils contaminated with diesel oil and gasoline. According to Gospodarek et al [38], this effect varies depending on the contaminant substance, the specific enzyme analyzed, and the duration of pollutant persistence in the soil.…”
Section: Introductionsupporting
confidence: 91%
“…Research by Borowik et al [35], Borowik et al [19], and Wyszkowska et al [36] indicate that diesel oil stimulates the activity of soil enzymes. Similar results were reported by Goma-Tchimbakala et al [37], who observed high activities of β-glucosidase, β-glucosaminidase, and acid phosphatase in soils contaminated with diesel oil and gasoline. According to Gospodarek et al [38], this effect varies depending on the contaminant substance, the specific enzyme analyzed, and the duration of pollutant persistence in the soil.…”
Section: Introductionsupporting
confidence: 91%